Neanic acceleration in Nephrolepidina from the Oligo-Miocene Mt. Torretta section (L'Aquila, central Apennines): biometric results and evolutionary, taxonomic and biostratigraphic remarks. - Schiavinotto, Francesco (Journal of Mediterranean Earth Sciences, 2016)
A sequence of eighteen Nephrolepidina populations, coming from the Oligo-Miocene outcrop of Mt. Torretta (L’Aquila - central Apennines), are investigated applying the biometric analysis on the embryo-nepionic chambers and on the fifth stage of the neanic equatorial chamberlets, supplying additional data about parameters and factors that had already demonstrated to have taxonomic-biostratigraphic significance. The occurrence of the whole sequence of different evolutionary stages, Nephrolepidina praemarginata – N. morgani – N. tournoueri, is confirmed. These chronospecies, characterizing the Mediterranean lineage, follow an evolutionary development according to the principles of “embryonic and nepionic accelerations”. The data evidence that the “Degree of stolonic distalization” (Factor FD5) and the “Shape Index” (Factor SI5), measured at the 5th neanic stage, have a very good fitting with the previously evidenced overall trend to elongate the shape of the equatorial chamberlets, connected with their packing (Golden Selection) and a gradually more distal position of the radial stolons (Neanic acceleration). However, according to the biometrical investigation of embryo-nepionic apparatuses, there are significant taxonomic issues, hampering an effective application of the genus to high-resolution biostratigraphy. Both the typological and the quantitative specific, phylogenetic and biostratigraphic definitions, could be improved by means of an integration of the embryonic-nepionic-neanic data. In that way, a significant preliminary goal is reached, suggesting two new, tentative, preliminary biometric boundaries between the chronospecies.